Pengaruh Modal Sendiri dan Modal Pinjaman Terhadap Laba Usaha (Studi Kasus Pada Bengkel Motor Marsel Bungamas, Kecamatan Kikim Timur) - Jhenny Wulandari; Saparudin Saparudin; Melia Andayani (Jurnal Multidisiplin Dehasen (MUDE), 2026)
This study aims to analyze the effect of equity capital and loan capital on business profit at Marsel Motorcycle Workshop in Bungamas Village, Kikim Timur District. The research used financial report data from 2022 to 2024, employing an associative quantitative method with multiple linear regression analysis using SPSS version 25. The results show that equity capital has no significant effect on business profit, and loan capital also has no significant effect on business profit. The simultaneous test (F-test) indicates that both independent variables do not jointly influence business profit. The coefficient of determination (R²) of 1% indicates that only a small portion of the variation in business profit can be explained by equity capital and loan capital, while the remaining 99% is influenced by other factors outside this study. Based on these findings, it is recommended that business owners improve financial management and consider non-capital factors such as service quality, marketing strategies, and employee competence to enhance business profit.